The Effect of Hydration on the Structure and Transport Properties of Confined Carbon Dioxide and Methane in Calcite Nanopores - Mohammed, Sohaib; Gadikota, Greeshma (Frontiers in Energy Research, 2018)
The effect of hydration on the structure and transport properties of confined carbon dioxide (CO2) and methane (CH4) in 2 nm slit-shaped calcite nanopore was studied using molecular dynamics simulations. The effect of no confined water, one layer of confined water composed of 150 water molecules, 500 water molecules, and 1,296 water molecules that correspond to the density of bulk water of 1 g/cm3 on the structural arrangement and diffusivity of confined CO2 and CH4 were investigated. Higher number of water molecules in confinement influenced the anisotropic distribution of the confined gases by displacing the adsorbed gas molecules away from the pore surface toward the pore center. The diffusivities of CO2 and CH4 were influenced by the density of confined water and were found to vary anisotropically in the calcite nanopores. In the absence of confined water, the enhanced affinity of CO2 for the calcite interface is influenced by van der Waals and electrostatic interactions. In the case of CH4, van der Waals energetic interactions contribute to the affinity to the calcite interface. In the presence of interfacial water with a density similar to that of bulk water, the van der Waals contributions arising from gas interactions with the calcite interface are much smaller compared to the van der Waals contributions arising from interactions with the water. In case of CO2, the van der Waals and electrostatic interactions arising from interactions with water contribute to CO2 solvation. However, the van der Waals interactions are the primary contributors to CH4 solvation in confined water.